A systematic review of the effect of the integration of speech therapy with music therapy on swallowing for patients with Parkinson’s disease - Wanicharoen, Natwipa; Boonrod, Vich; Songdechagraiwud, Erin; Yaemsuan, Palita (Journal of Associated Medical Sciences, 2025)
Background: Dysphagia, or swallowing impairment, is a common complication in individuals with Parkinson’s disease. Speech therapy is a non-pharmacological intervention that employs behavioral techniques to address this condition. A growing body of research also suggests that music therapy may have beneficial effects on swallowing function in this population. However, the effectiveness of integrating speech and music therapy for improving swallowing in individuals with Parkinson’s disease has not yet been systematically evaluated. Objectives: The objective of this systematic review was to examine the effectiveness of integrating speech therapy with music therapy for swallowing in patients with Parkinson’s disease. Materials and methods: This study was registered in PROSPERO (CRD420251118370) and performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). A total of two studies met the inclusion criteria. The authors systematically reviewed four electronic databases: PubMed, CINAHL Complete, the Cochrane Library, and Google Scholar. A hand search of the reference list of related articles was performed to identify any additional eligible studies. The assessment of bias risk was conducted using the Joanna Briggs Institute’s (JBI) critical appraisal tools. Results: A total of two studies investigated the effects of speech therapy in combination with music therapy. One study implemented an interdisciplinary choral singing therapy program that included vocal exercise and choral singing. The other study applied a conventional speech therapy protocol-specifically, Lee Silverman Voice Treatment (LSVT LOUD®) and vocal exercises-combined with music therapy incorporating motor, breathing, vocal, and singing exercises. The integration of speech and music therapy demonstrated promising results in improving swallowing function in individuals with Parkinson’s disease. Conclusion: The findings highlight the potential benefits of integrating speech and music therapy to improve swallowing function in individuals with Parkinson’s disease. However, due to the limited number of studies and methodological heterogeneity, definitive conclusions regarding the most effective intervention components cannot yet be drawn. While encouraging, the current evidence underscores the need for further high-quality research particularly randomized controlled trials to establish standardized protocols. Advancing this interdisciplinary approach may enhance rehabilitation outcomes and improve quality of life for this population.